Effect of exercise training on modulating the TH17/TREG imbalance in individuals with severe COPD: A randomized controlled trial - Juliana Tiyaki Ito; Luan Henrique Vasconcelos Alves; Luana de Mendonça Oliveira; Rafaella Fagundes Xavier; Regina Maria Carvalho-Pinto; Iolanda de Fátima Lopes Calvo Tibério; Maria Notomi Sato; Celso R. F. Carvalho; Fernanda Degobbi Tenorio Quirino dos Santos Lopes (Pulmonology)
Background Chronic obstructive pulmonary disease (COPD) induces an imbalance in T helper (Th) 17/regulatory T (Treg) cells that contributes to of the dysregulation of inflammation. Exercise training can modulate the immune response in healthy subjects.Objective We aimed to evaluate the effects of exercise training on Th17/Treg responses and the differentiation of Treg phenotypes in individuals with COPD.Methods This randomized controlled trial included 50 individuals with severe or very severe COPD who were allocated to the Exercise or Control groups. The Exercise group underwent eight weeks of aerobic and muscle strength training, whereas the Control group received usual care. The primary outcome was the change in the phenotypic characteristics of Tregs and Th17 profile differentiation in systemic inflammation.Results Exercise training increased the frequency of total and activated Tregs and decreased the frequency of Th17 cells in between-group comparisons. Additionally, Th17/Treg responses were moderately correlated with improvements in the six-minute walking test, muscle strength of the upper and lower limbs, and daily life physical activity levels.Conclusion Exercise training improved functional exercise capacity, muscle strength, and physical fitness, which was associated with a decrease in the Th17 inflammatory response and an increase in Treg cell phenotypes immunosuppressive activity.